L-cysteine embedded core-shell ZnO microspheres composed of nanoclusters enhances anticancer activity against liver and breast cancer cells. (December 2022) - Wahab, Rizwan; Khan, Farheen; Kaushik, Neha; Kaushik, Nagendra Kumar; Nguyen, Linh Nhat; Choi, Eun Ha; Siddiqui, Maqsood A.; Farshori, Nida Nayyar; Saquib, Quaiser; Ahmad, Javed; Al-Khedhairy, Abdulaziz A.
Abstract: Nano-based products have become an apparent and effective option to treat liver cancer, which is a deadly disease, and minimize or eradicate these problems. The Core-shell ZnO microspheres composed of nanoclusters (ZnOMS-NCs) have shown that it is very worthwhile to administer the proliferation rate in HepG2 and MCF-7 cancer cells even at a very low concentration (5 μg/mL). ZnOMS-NCs were prepared through hydrothermal solution process and well characterized. The MTT assay revealed that the cytotoxic effects were dose-dependent (2.5 μg/mL-100 μg/mL) on ZnOMS-NCs. The diminished activity in cell viability induces the cytotoxicity response to the ZnOMS-NCs treatment of human cultured cells. The qPCR data showed that the cells (HepG2 and MCF-7) were exposed to ZnOMS-NCs and exhibited up-and downregulated mRNA expression of apoptotic and anti-apoptotic genes, respectively. In conclusion, flow cytometric data exhibited significant apoptosis induction in both cancer cell lines at low concentrations. The possible mechanism also describes the role of ZnOMS-NCs against cancer cells and their responses. Graphical abstract: A representative image shows the nanoclusters formation and their activity against cancer cells Unlabelled Image Highlights: Core-shell ZnO microspheres were utilized against HepG2 and MCF-7 cancer cells. The anticancer activity was investigated from 2.5 to 100 μg/mL against HepG2 and MCF-7 cancer cells. The MTT assay discloses that 80% reduction of cancer cells was achieved with NCs at 5 μg/mL. The G2/M arrest was found in HepG2 whereas increase in SubG1 apoptotic peak in MCF-7 cells. The up ( bax, cas3, p53 ) and down ( bcl-2) regulations were observed at 5 μg/mL NCs.